2020
DOI: 10.1093/femsle/fnaa036
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of the roles of AgrA and σB regulators in Listeria monocytogenes adaptation to roots and soil

Abstract: Little is known about the regulatory mechanisms that ensure the survival of the food-borne bacterial pathogen Listeria monocytogenes in the telluric environment and on roots. Earlier studies have suggested a regulatory overlap between the Agr cell–cell communication system and the general stress response regulator σB. Here, we investigated the contribution of these two systems to root colonisation and survival in sterilised and biotic soil. The ability to colonise the roots of the grass Festuca arundinacea was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…A subset of approximately 60 genes, identified across strains of L. monocytogenes belonging to different lineages, constitute the σ B core regulon ( Oliver et al, 2010 ). Genes comprising the σ B regulon are involved in carbohydrate metabolism ( Abram et al, 2008b ; Tapia et al, 2020 ), cell envelope modification ( Abram, 2007 ; Tiensuu et al, 2013 ), pH homeostasis ( Cotter et al, 2005 ; Karatzas et al, 2010 , 2012 ), osmoregulation ( Fraser et al, 2003 ; Cetin et al, 2004 ; Wemekamp-Kamphuis et al, 2004 ; Abram et al, 2008a ), regulation of amino acids biosynthesis ( Marinho et al, 2019 ), flagellar biosynthesis ( Raengpradub et al, 2008 ; Toledo-Arana et al, 2009 ), quorum sensing ( Marinho et al, 2020 ), and antibiotic resistance ( Begley et al, 2006 ). These mechanisms under σ B control have been previously reviewed ( O’Byrne and Karatzas, 2008 ; NicAogáin and O’Byrne, 2016 ; Dorey et al, 2019b ; Liu et al, 2019 ), and they contribute to the survival of L. monocytogenes under a broad range of lethal stresses ( Cole et al, 1990 ; Ferreira et al, 2001 ; Sue et al, 2003 ; Wemekamp-Kamphuis et al, 2004 ; Begley et al, 2005 , 2006 ; Giotis et al, 2008 ; Palmer et al, 2009 ; Shin et al, 2010a ; Dowd et al, 2011 ; Feehily et al, 2012 , 2013 , 2014 ; O’Donoghue et al, 2016 ; Curtis et al, 2017 ; Bourke et al, 2019 ; Williams et al, 2019 ).…”
Section: σ B -Dependent Robustness In Lmentioning
confidence: 99%
“…A subset of approximately 60 genes, identified across strains of L. monocytogenes belonging to different lineages, constitute the σ B core regulon ( Oliver et al, 2010 ). Genes comprising the σ B regulon are involved in carbohydrate metabolism ( Abram et al, 2008b ; Tapia et al, 2020 ), cell envelope modification ( Abram, 2007 ; Tiensuu et al, 2013 ), pH homeostasis ( Cotter et al, 2005 ; Karatzas et al, 2010 , 2012 ), osmoregulation ( Fraser et al, 2003 ; Cetin et al, 2004 ; Wemekamp-Kamphuis et al, 2004 ; Abram et al, 2008a ), regulation of amino acids biosynthesis ( Marinho et al, 2019 ), flagellar biosynthesis ( Raengpradub et al, 2008 ; Toledo-Arana et al, 2009 ), quorum sensing ( Marinho et al, 2020 ), and antibiotic resistance ( Begley et al, 2006 ). These mechanisms under σ B control have been previously reviewed ( O’Byrne and Karatzas, 2008 ; NicAogáin and O’Byrne, 2016 ; Dorey et al, 2019b ; Liu et al, 2019 ), and they contribute to the survival of L. monocytogenes under a broad range of lethal stresses ( Cole et al, 1990 ; Ferreira et al, 2001 ; Sue et al, 2003 ; Wemekamp-Kamphuis et al, 2004 ; Begley et al, 2005 , 2006 ; Giotis et al, 2008 ; Palmer et al, 2009 ; Shin et al, 2010a ; Dowd et al, 2011 ; Feehily et al, 2012 , 2013 , 2014 ; O’Donoghue et al, 2016 ; Curtis et al, 2017 ; Bourke et al, 2019 ; Williams et al, 2019 ).…”
Section: σ B -Dependent Robustness In Lmentioning
confidence: 99%
“…Experiments in our lab suggest Lm can reach populations of 10 6 –10 7 CFU/plant following root inoculation of F . arundinacea and C. cajan (Marinho et al, 2020; Sharma et al, 2020) and confocal microscopy observations confirmed that Lm can establish as biofilms (L. Gal et al, personal communication).…”
Section: Plants Offer Suitable Habitats For the Persistence Of Lister...mentioning
confidence: 94%
“…Nonedible plants can be colonized by Lm. For example, Arabidopsis thaliana (Milillo et al, 2008), Festuca arundinacea (Marinho et al, 2020), Cajanus cajan (Sharma et al, 2020), and Medicago truncatula (Figure 2a) can support Lm growth. Experiments in our lab suggest Lm can reach populations of 10 6 –10 7 CFU/plant following root inoculation of F .…”
Section: Plants Offer Suitable Habitats For the Persistence Of Lister...mentioning
confidence: 99%
“…In farm environments the causative agent of listeriosis, L monocytogenes, was reported to express high resilience to different waste treatments, plus was still present for more than a month in amended soils even without livestock effluents (Hutchison et al, 2005;Moynihan et al, 2015). It has been shown that the bacterium's adaptability to soil environments can be reduced through the impairment of AgrA gene expression, which regulates motility, chemotaxis, transport and metabolism of amino acids (Marinho et al, 2020). Specifically, AgrA and σB factors control the general stress response and can cooperatively modulate the L. monocytogenes transcriptome to induce a more precise adaptation and an optimal growth and survival rate.…”
Section: Listeria Sppmentioning
confidence: 99%